N′-(4-Bromobenzylidene)isonicotinohydrazide - Li, Li-Min (International Union of Crystallography, 2008)
The title compound, C(13)H(10)BrN(3)O, was prepared by the reaction of isonicotinohydrazide and 4-bromobenzaldehyde. The dihedral angle between the benzene and pyridine rings is 8.60 (12)°. The crystal packing is stabilized by intermolecular C—H⋯O and N—H⋯O hydogen-bonding interactions.